13.9k views
0 votes
2) Rearrange the Pythagorean Theorem to solve first for c and then y.

2) Rearrange the Pythagorean Theorem to solve first for c and then y.-example-1

1 Answer

7 votes

Answer:


x=z-√(-y) , or, x^2=z^2-y^2\\y=z-√(-x), or, y^2=z^2-x^2

Explanation:

I can't do much except put the Pythagorean theorem in terms of y or x.

All I did was isolate x or y by subtracting the, x or y variable from each side.


-(y^2)+x^2 +y^2=z^2-(x^2)\\-(y^2)+x^2 +y^2=z^2-(y^2)

Which tuns it into:


x^2=z^2-y^2\\y^2=z^2-x^2

And I isolated further by squaring each side, but squaring negative number is difficult and causes imaginary numbers so I just think it should stay as all of them to the power of two.

User Tatranskymedved
by
5.4k points